10.1016/s1541-9800(09)70409-0 (CrossRef Listing of Deleted DOIs, 2000)
The study aimed to explore the lived experiences of married dialysis patients on the national organ waiting list, focusing on the interplay between illness, familial roles, and societal norms. This research is a qualitative study using semi-structured interviews and participant observation. The study involved 23 marriage-experienced hemodialysis-dependent patients (13 women, 10 men) on the national organ waiting list, recruited between August 16 and November 11, 2022. Data were collected through interviews and observations and were analyzed thematically to identify recurring patterns. Chronic kidney disease (CKD) poses significant physical, psychological, and social burdens, particularly for hemodialysis-dependent patients. Five main themes emerged from this study: (1) When Care Becomes a Test, (2) Dealing with Social Isolation, (3) Sacrifices to Sustain the Marriage, (4) Uninvited voices, (5) Resentful but Thankful. These findings highlight the need for family-centered care that considers diverse family structures and social contexts, while also demonstrating the impact of prolonged hemodialysis (HD) and marital strain on emotional and sexual intimacy.